2019
DOI: 10.3847/2041-8213/ab30ca
|View full text |Cite
|
Sign up to set email alerts
|

Possible Early Linear Acceleration of Proto-neutron Stars via Asymmetric Neutrino Emission in Core-collapse Supernovae

Abstract: In this Letter, we present the result of an axisymmetric CCSN simulation conducted with appropriate treatments of neutrino transport and proper motions of proto-neutron star (PNS), in which a remarkable PNS acceleration is observed in association with asymmetric neutrino emissions by the time of 300ms after bounce. We find that these asymmetric neutrino emissions play important roles in the acceleration of PNS in this phase. The correlation between the PNS proper motion and the asymmetric ejecta is similar to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 41 publications
5
69
0
Order By: Relevance
“…Realistic models.-Below we vindicate the above argument given for the bulb model by quantitatively analyzing the data obtained in our CCSN simulations with the full Boltzmann neutrino transport. Importantly, the ELN crossings in the pre-shock region are confirmed in many of our models [47,48] and also in those of Garching group, which are publicly available [49]. Tamborra et al [18] reported that there was no ELN crossing in the latter models, which is not true, however.…”
supporting
confidence: 68%
“…Realistic models.-Below we vindicate the above argument given for the bulb model by quantitatively analyzing the data obtained in our CCSN simulations with the full Boltzmann neutrino transport. Importantly, the ELN crossings in the pre-shock region are confirmed in many of our models [47,48] and also in those of Garching group, which are publicly available [49]. Tamborra et al [18] reported that there was no ELN crossing in the latter models, which is not true, however.…”
supporting
confidence: 68%
“…The pattern in α is (anti)correlated with a similar pattern in Y e (and T ) that appears very deep inside the PNS and is thought to be caused by the convectional flows therein. This is closely related to LESA [47][48][49][50][51][52][53][54][55] in which strong dipole structure exists in the neutrino distributions which can be preceded by strong higher multipole structures at earlier times. Our study suggests that if the multipole structures (either dipole at later times or higher multipoles at earlier times) are strong enough, they can lead to the existence of zones with significantly large α's and a good chance for the occurrence of ELN crossings.…”
Section: Discussionmentioning
confidence: 74%
“…However, this story can be changed in multidimensional (multi-D) SN models. Indeed, recent multi-D SN simulations have shown that the neutrino distributions can be highly asymmetric in the presence of lepton-emission self-sustained asymmetry (LESA) [47][48][49][50][51][52][53][54][55]. Such asymmetric neutrino distributions can significantly help increasing the chance of the occurrence of ELN crossings by providing SN zones with smaller difference between nν e and n νe [56].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that large-scale coherent motions can be triggered by the random breaking of global symmetry in the shocked envelope, not necessarily first in the PNS convective zone, and that asymmetries in the latter might be a consequence of the former. Moreover, such symmetry breaking might be correlated with the PNS kick direction, as suggested by Nagakura et al (2019c). In- Figure 8.…”
Section: Turbulence In Pns Convectionmentioning
confidence: 89%